EFEKTIVITAS VIDEO ANIMASI DALAM PEMBELAJARAN KETERAMPILAN 2 BERBICARA MURID KELAS IV SD NEGERI 77 KANAENG KECAMATAN GALESONG SELATAN KABUPATEN TAKALAR - Jumriani; Rosmini Madeamin; Anzar (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
his study aims to determine the effectiveness of using animated video media in improving the speaking skills of fourth-grade students at SD Negeri 77 Kanaeng, South Galesong District, Takalar Regency. The study used a quantitative approach with a pre-experimental One Group Pretest-Posttest Design. The sample consisted of 23 fourth-grade students selected using random sampling. Data collection techniques included speaking skills tests (pre-test and post-test), observation, questionnaires, and documentation. Data analysis used descriptive and inferential statistics with a paired t-test. The results showed that the average pretest score was 59.3, a low score, while the posttest score increased to 83.6, a high score. The paired t-test yielded a t-count of -11.770 with a significance level of 0.000 <0.05, indicating a significant difference between the pretest and posttest results. Furthermore, student activity and responses to the use of animated videos were also positive. Thus, it can be concluded that animated video media is effective in improving the speaking skills of fourth-grade students at SD Negeri 77 Kanaeng, South Galesong District, Takalar Regency.